Penerapan Pembelajaran Kolaboratif Dalam Mata Kuliah Bahasa Indonesia - Inka Piola Naretin Rahayu; Aura Yandira Utami; Anggita Ardiani Efendi Nasution; Nuraini Nuraini; Kurnia Riski Siregar; Muhammad Anggie J. Daulay (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This research describes the application of collaborative learning in Indonesian language courses at universities, identifies its benefits, and identifies the challenges faced in its implementation. This research also aims to formulate solutions that can overcome these challenges, thereby strengthening the effectiveness and success of collaborative learning in the context of teaching Indonesian in higher education. Based on the results and discussion, the conclusion that can be drawn is that collaborative learning has a strong theoretical basis from social constructivism, constructivism, social learning, and cooperative theory (Vygotsky, Piaget, Bandura, Johnson & Johnson). The implementation of collaborative learning provides significant benefits for students and lecturers, including increased motivation, material knowledge, engagement, and better interpersonal relationships. Effective implementation strategies include clarifying learning objectives, forming effective groups, providing structured assignments, facilitating interaction, and providing fair assessments. Further training and provision is needed for students and lecturers in implementing collaborative learning effectively. The development of assessment instruments that are more detailed and sensitive to individual contributions in the group can increase the objectivity of the assessment. Further research is needed to identify more efficient strategies for overcoming challenges in collaborative learning. Stronger support from universities in providing the training and resources needed to optimize the implementation of collaborative learning models